QUALITY CRITERIA FOR MINIMALLY MANIPULATED BIOTECHNOLOGICAL PRODUCTS BASED ON AUTOLOGOUS BONE MARROW ASPIRATE FOR USE IN TRAUMATOLOGY AND ORTHOPEDICS - Strafun, Sergiy; Holiuk, Yevhen; Zubov, Dmytro; Magomedov, Oleksandr; Starodub, Halyna; Malova, Hrystyna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Autologous biotechnological products based on bone marrow (BM) are a source of stem cells, in particular, hematopoietic and multipotent mesenchymal stromal cells, and act as one of the alternative therapeutic agents that can slow cartilage degeneration, improve its repair and, ultimately, prevent joint replacement. Objective. To develop quality and safety criteria of minimally manipulated biotechnological products from autologous bone marrow for use in patients with pathology of the musculoskeletal system. Methods. The material for the development of quality and safety criteria for the manufacture and use of biotechnological products from autologous red bone marrow aspirate was 85 patients with osteoarthritis and aseptic necrosis of the hip and knee joints, who used biotechnological products made from it. Cell counts in the myelogram and CFU-analysis of MMSCBM were performed in all patients. Results. As a result of the development of quality and safety criteria for biotechnological products from BM aspirate, 3 types of it were established: 1 — polymorphic (with the presence of progenitor cells of all types within the normal range), 2 — moderately cellular (with the presence of all types of progenitor cells, but some of them below the norm), 3 — hypocellular (with the presence of most types of progenitor cells, some of them below the norm). Functional quality criteria of biotechnological products from BM aspirate were developed on the basis of CFU-analysis and calculation of seeding efficiency coefficient (KEP) of MMSK-BM. Conclusions. Quality and safety criteria of biotechnological products based on autologous bone marrow aspirate based on the results of myelograms and CFU analysis have been established. According to the results of myelograms, type 1 BM aspirate was evaluated as excellent for the further manufacture of a biotechnological product, type 2 — good, type 3 — satisfactory. According to the results of the KUOf analysis, the KEP indicator ˂ 0.001 % was evaluated as unsatisfactory, the KEP indicator within the range of 0.001–0.003 % — satisfactory, the KEP indicator ˃ 0.003 % — good. The KEP ˂ 0.001 % — unsuitable for use.